Achat et rachat d'actions en vertu de la Loi régissant les sociétés commerciales canadiennes - Demers, Robert (Les Cahiers de droit, 1981)
The power to purchase its own shares by a corporation constitutes the most remarkable innovation in recent company legislations throughout Canada. This article deals primarily with the power to acquire shares under the Canada Business Corporations Act and the exercise of this power, subject to various conditions relating to the corporation's solvency and directors' duties. In a wider perspective, the rights of creditors of the corporation are analysed and the clear transition from a concept of the corporate capital as a trust fund for creditors to a concept of capital as a practical planning device emerges from the analysis.